Vida em condomínio: a construção de vínculos no ambiente de moradia - Carvalho, Cecilia Côrtes (2018)
This study seeks to understand the meaning attributed to the ties of residents of a gated community with their living environment. It is a qualitative research of multiple cases, that used the theory of attachment and the systemic perspective as a theoretical basis. The survey was conducted in a gated community on the outskirts of the city of São Paulo, with approximately six years of construction, seven towers of five floors each, and a total of 270 apartments. There were five participants, whose narratives were submitted to thematic analysis. The meaning of the themes reported the quality of the resident-housing interrelationship. The results showed that the place of housing, in the configuration of gated vertical community, represents a safe environment, since its physical and social security equipment promotes the feeling of protection in the face of fears imparted by the streets, the city — all that is beyond the walls and that escapes the control of the 24-hours surveillance and security system. A secure place bond appears as a protective factor for mental health and a resilience tutor. Housing, like family, can be the social, as well as the geographical reference for someone and still anchor the continuous process of construction of subjectivity. This study brought invisible links to the Psychology map: where apparently there was no bonds — housing in a gated community —, there are structured bonds that function in accordance with the degree of intimacy and sense of security provided by the interaction of the residents